2009
DOI: 10.4049/jimmunol.0903306
|View full text |Cite
|
Sign up to set email alerts
|

IL-33 Induces IL-13–Dependent Cutaneous Fibrosis

Abstract: IL-33 is constitutively expressed in epithelial barrier tissues, such as skin. Although increased expression of IL-33/IL-33R has been correlated with fibrotic disorders, such as scleroderma and progressive systemic sclerosis, the direct consequences of IL-33 release in skin has not been reported. To determine the effects of dysregulated IL-33 signaling in skin, we administered IL-33 s.c. and monitored its effects at the injection site. Administration of IL-33 resulted in IL-33R–dependent accumulation of eosino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
156
3
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(165 citation statements)
references
References 75 publications
3
156
3
3
Order By: Relevance
“…IL-13, a recognized M2 differentiation factor that is released by eosinophils upon IL-33 stimulation, can be responsible, at least in part, for the increased differentiation of M2 macrophages. During the preparation of this manuscript and consistent with our data, it was reported that IL-33 can trigger the production of IL-13 from eosinophils and that this was important in eosinophil-and macrophage-driven fibrosis (50). Interestingly, IL-33 administered locally into the lungs helps to retain a significant proportion of adoptively transferred eosinophils, probably due to an induction of chemokines (e.g., CCL24 and CCL3) in the airways.…”
Section: Discussionsupporting
confidence: 72%
“…IL-13, a recognized M2 differentiation factor that is released by eosinophils upon IL-33 stimulation, can be responsible, at least in part, for the increased differentiation of M2 macrophages. During the preparation of this manuscript and consistent with our data, it was reported that IL-33 can trigger the production of IL-13 from eosinophils and that this was important in eosinophil-and macrophage-driven fibrosis (50). Interestingly, IL-33 administered locally into the lungs helps to retain a significant proportion of adoptively transferred eosinophils, probably due to an induction of chemokines (e.g., CCL24 and CCL3) in the airways.…”
Section: Discussionsupporting
confidence: 72%
“…In addition to Th2 cells, IL-33 has been shown to act on macrophages (9), dendritic cells (10), mast cells (11), basophils (12), eosinophils (13), natural helper cells (14), nuocytes (15), and multipotent progenitors (16). Even though IL-33 functions as a key mediator for Th2-mediated asthma and fibrosis (17), IL-33 is also a crucial cytokine for chronic inflammatory arthritis that integrates the activation of fibroblasts and Th1 and Th17 effector T cells operating through a mast cell-dependent pathway (18).…”
mentioning
confidence: 99%
“…To the best of our knowledge, the present study is the first to report that IL-33/ST2 signaling exist in a murine model of bleomycininduced pulmonary fibrosis. It is also the first study that to report that Saikosapoin-D has some degree of interference in IL-33/ST2 signaling pathway, compared to other studies that found that IL-33/ST2 signaling pathway was interfered by anti-IL-33 antibody [21] or soluble ST2 [22], or administration of IL-33 [23].…”
Section: Discussionmentioning
confidence: 95%